Plasmonic colloidal pastes for surface-enhanced Raman spectroscopy (SERS) of historical felt-tip pens. Issue 15 (22nd February 2018) - Saviello, Daniela; Alyami, Abeer; Trabace, Maddalena; Giorgi, Rodorico; Baglioni, Piero; Mirabile, Antonio; Iacopino, Daniela
Abstract : SERS analysis performed with silver nanopastes allowed in situ identification of dye compositions of the historical felt-tip pens used by Federico Fellini. Abstract : Surface-enhanced Raman spectroscopy (SERS) has been identified as a suitable technique for the analysis of colorants in works of art. Herein, the application of SERS to the identification of dye compositions in historical felt-tip pens is reported, which is of paramount importance for the development of appropriate conservation protocols for historical drawings. In this study, three pens (pink, green, and blue colors) belonging to the film director Federico Fellini were analyzed. SERS measurements were performed directly on the pen lines drawn on a commercial paper by the deposition of Ag colloidal pastes, which allowed fast in situ dye identification without the need for extraction or hydrolysis treatments. Eosin Y was identified as the only dye present in the pink pen ink, whereas erioglaucine was found to be the main dye component in green and blue pen inks. SERS also resulted in highly efficient identification of the individual dyes erioglaucine, crystal violet, and rhodamine present as a mixture in the blue pen ink. The high SERS sensitivity was ascribed to the plasmonic effects and efficient quenching of the fluorescence interference of dyes. A comparison with contemporary pen inks highlighted minor differences in the chemical composition. These results prove that SERS can be used as a fast and sensitive analytical tool for ink analysis that provides invaluable support for the general assessment of the date, provenance, and originality of the historical drawings as well as for the development of preventive conservation protocols.